Characteristics of the nitric oxide system indicators in the left ventricle myocardium in SHR - Yu. M. Kolesnyk; M. I. Isachenko; O. V. Melnikova; T. A. Hrekova (Zaporozhye State Medical University, 2019)
The aim was to determine the morpho-functional parameters of the left ventricular myocardium NO system in the rats with essential hypertension (SHR line). Material and methods. We used a combination of modern highly informative methods, namely: research of NOS isoform profie (nNOS, iNOS eNOS) in the myocardial slices along with an assessment of their synthesis and expression of the corresponding mRNA; NO derived nitrites level determination directly in the myocardium homogenates and concentration of nitrotyrosine in blood plasma of rats. The results of the performed studies have shown that high blood pressure in the SHR was accompanied by a signifiant increase in the concentrations of all three NOS isoforms in the myocardium and increased expression of their mRNA. Higher concentration of nitrites by 18.8 % was detected in the SHR group compared with the control animals. The concentration of nitrotyrosine in blood plasma of rats with essential hypertension was also increased by 25 %. Conclusions. The predominance of IRM to constitutive isoforms of NOS with low IRM content to iNOS was noted in the myocardium of the control group rats while in SHR rats higher IRM values were marked for all NOS isoforms. The formation of hypertension is accompanied by high content of NO end metabolites and the development of systemic nitroso-oxidative stress with the increase of nitrotyrosine concentration.